Private equity investmenr cmmittee par on Sogrape, SGPS, S.Aper - Neves, Francisco Xavier Robles Machado Duarte (2020)
This work project aims to study a private equity deal of the Portuguese company Sogrape using a Leverage Buyout Model. The evaluation of the deal includes the studying of the company and the industry in which it operates, followed by the description of the investment thesis and the business plan. After a valuation of the company is made, as well as capital structure is defined, returns and sensitivities are computed. Finally, exit options are evaluated. The following deck contains a detailed analysis of Sogrape as a company. This includes a brief profile, as well as analysis of operations, strategy and financials throughout the past years. The analysis is of paramount importance since it will serve as the major building block for the entire investment thesis.